Charcoal‐inferred Holocene fire and vegetation history linked to drought periods in the Democratic Republic of Congo. (6th February 2015) - Hubau, Wannes; Van den Bulcke, Jan; Van Acker, Joris; Beeckman, Hans
Abstract The impact of Holocene drought events on the presumably stable Central African rainforest remains largely unexplored, in particular the significance of fire. High‐quality sedimentary archives are scarce, and palynological records mostly integrate over large regional scales subject to different fire regimes. Here, we demonstrate a direct temporal link between Holocene droughts, palaeofire and vegetation change within present‐day Central African rainforest, using records of identified charcoal fragments extracted from soil in the southern Mayumbe forest (Democratic Republic of Congo). We find three distinct periods of local palaeofire occurrence: 7.8–6.8 ka BP, 2.3–1.5 ka BP, 0.8 ka BP – present. These periods are linked to well‐known Holocene drought anomalies: the 8.2 ka BP event, the 3rd millennium BP rainforest crisis and the Mediaeval Climate Anomaly. During and after these Holocene droughts, the Central African rainforest landscape was characterized by a fragmented pattern with fire‐prone open patches. Some fires occurred during the drought anomalies although most fires seem to lag behind them, which suggests that the open patches remained fire‐prone after the actual climate anomalies. Charcoal identifications indicate that mature rainforest patches did persist through the Early to Mid‐Holocene climatic transition, the subsequent Holocene thermal optimum and the third millennium BP rainforest crisis, until 0.8 ka BP. However, disturbance and fragmentation were probably more prominent near the boundary of the southern Mayumbe forest. Furthermore, the dominance of pioneer and woodland savanna taxa in younger charcoal assemblages indicates that rainforest regeneration was hampered by increasingly severe drought conditions after 0.8 ka BP. These results support the notion of a dynamic forest ecosystem at multicentury time scales across the Central African rainforest.